2019
DOI: 10.7575/aiac.ijalel.v.8n.2p.113
|View full text |Cite
|
Sign up to set email alerts
|

Does High Anxiety Decrease Motivation for Learning English as a Foreign Language?

Abstract: This study investigates the relationship between the level of foreign language anxiety experienced by Saudi female English learners at a Saudi university and the level of their motivation in learning English as a foreign language. The participants were 40 female second-year university students. The instruments the researchers used to gather the data were two questionnaires: Horwitz, Horwitz, and Cope’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) and Gardner’s (2006) Attitude/Motivation Test Battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Their study samples included participants of both genders; a dedicated female research assistant was hired to recruit and collect data from female participants in each of the two studies. Nonetheless, some of the studies that we have discussed here (e.g., Almurshed & Aljuaythin, 2019;Al Yami, 2015;Fodah, 2013;Massri, 2017) are vulnerable to criticism concerning the size of their participant samples.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Their study samples included participants of both genders; a dedicated female research assistant was hired to recruit and collect data from female participants in each of the two studies. Nonetheless, some of the studies that we have discussed here (e.g., Almurshed & Aljuaythin, 2019;Al Yami, 2015;Fodah, 2013;Massri, 2017) are vulnerable to criticism concerning the size of their participant samples.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between learner anxiety and other emotional factors has been investigated in the Saudi setting. A study by Almurshed and Aljuaythin (2019) revealed completely contradictory findings in relation to the association between learner anxiety and motivation: learners were found to be highly motivated to learn English but reported experiencing high levels of FLA. This surprising finding contradicted a well-established conclusion in the L2 research (see, e.g., Liu, 2012;Tahernezhad, Behjat, & Kargar, 2014) that language anxiety is negatively correlated with language motivation (i.e., high levels of language anxiety usually lead to a low of motivation in learners, and vice versa).…”
Section: Research On L2 Anxietymentioning
confidence: 99%
“…Teniendo en cuenta los resultados encontrados entre el nivel de motivación alto y ansiedad lingüística media es posible contrastar esta investigación con en el estudio Does high anxiety decrease motivation for learning english as a foreign language? realizado porAlmurshed (2019) en el cual se investigó el rol de la motivación sobre el control de la ansiedad y su relación en el aprendizaje de los idiomas extranjeros en 40 estudiantes saudíes utilizando el FLCASde Horwitz et al (1986) y el nivel de motivación usando el AMTB de Gardner(2006). SegúnAlmurshed (2019), los hallazgos revelaron altos niveles de ansiedad lingüística y altos niveles de motivación, interpretando estos resultados en que la ansiedad lingüística no es un predictor negativo de la motivación en el aprendizaje de idiomas, puesto que ambas variables coexistían entre sí.…”
unclassified